Occupational factors, life expectancy, and biotechnological and pharmacological health support strategies - Filiptsova, Olga; Naboka, Olga; Ochkur, Oleksandr; Dvinskykh, Nataliia; Soloviova, Alina; Kyrylo, Mosiichuk; Kravtsova, Oleksandra (ScienceRise: Biological Science, 2025)
The aim of the study was to analyze the associations of life expectancy and professions among prominent people of different historical periods, as well as some biotechnological and pharmacological aspects of promoting longevity. Materials and methods. The work used statistical analysis and descriptive-comparative analysis. Results and discussion. The analysis of the literature shows that the average human life expectancy is a variable value. Life expectancy for the period from 1800 to 2011 increased from 30 to 68 years, in 2016 it was 69 years; for men - 67 years, for women - 71.1 years. There are significant differences in the life expectancy of a person within each country. The factors that determine the average life expectancy relate to education, income, employment and profession, as well as other indicators of socio-economic status. 640 prominent people were selected for the study, including 537 men and 103 women. Prominent people were residents of 45 countries, the largest number of people in the USA - 255, Great Britain - 65, Ukraine - 49, France - 42, Germany - 33 individuals. Prominent people were divided into a group of living (109 people) and deceased (531 people). The average life expectancy of the living is 73.4 years and this is more than the average life expectancy of the deceased, their age is 72.3 years. During the work, it has been found that there are differences in the average life expectancy within each country, between professional groups. The average life expectancy of all prominent people in the study is 72.9 years. It has been found that among the professional groups in the study, politicians have the highest average life expectancy. The results of studies of average life expectancy in the relationship between gender and professional activity showed that for men this figure is 71.4, for women - 74.8 years. Conclusions. According to the results of the study, the average life expectancy of men is 71.9 years, and of women is 74.4 years. In the group of living people, the highest indicators of average life expectancy are programmers, and in the group of living and deceased prominent people, this indicator is highest among politicians. These data confirm scientific data on the dependence of life expectancy on gender and professional activity. In our further studies, we plan to study possible associations with diseases